The SISTEM INFORMASI MANAJEMEN MUTU DIGITAL UNTUK MEWUJUDKAN SEKOLAH UNGGUL: Studi Kasus di SMP Muhammadiyah Al Mujahidin - Pradikta, Zendy; Widodo, Hendro; Hasanah, Enung (Idaarah: Jurnal Manajemen Pendidikan, 2025)
The rapid digital transformation in education encourages schools to optimize quality management systems through technology. Responding to this, SMP Muhammadiyah Al Mujahidin implemented a Digital-Based Quality Management Information System (QMIS) in 2021 to support its vision of becoming an excellent school. This study aims to explore the implementation of digital-based QMIS through four management functions Planning, Organizing, Actuating, and Controlling (POAC) and to analyze its role in improving educational quality and academic achievement. Using a descriptive qualitative approach, data were collected from ten informants and analyzed with the Miles-Huberman interactive model, including data reduction, display, and conclusion drawing, with triangulation ensuring data validity. The results show that planning involved assessing digital needs, setting goals, and aligning instruments with school policy. Organizing was carried out through collaborative teamwork, adaptive stakeholder training, and performance-based rewards. Actuating emphasized discipline incentives, real-time data transparency, and technical support, while controlling involved periodic data verification and continuous system evaluation. QMIS has made a significant contribution to enhancing school accountability, administrative efficiency, religious culture, and digital collaboration between parents and the school. The research concludes that digital-based QMIS serves as a catalyst for achieving an excellent school when implemented through participative and adaptive POAC integration. This success is supported by visionary leadership, adequate infrastructure, and active stakeholder involvement. However, challenges remain, including improving senior teachers’ digital literacy and strengthening cloud security. Strategic recommendations include enhancing human resource capacity and continuing system innovation.